THE STUDY OF THE INTENSITY AND LUMINESCENCE SPECTRA (Y1-xYb0,1Erx)3Al5O12 WITH LASER EXCITATION - Egor Igorevich Pozdnyakov; Victor Andreevich Vorobyev (Вестник Северо-Кавказского федерального университета, 2022)
Studied the luminescent properties of solid solutions (Y1–xYb0,1Erx)3Al5O12, set the intensity of the Stokes IR luminescence in the range of 0,96–1,1 microns and 1,42–1,72 microns, the concentration of Er3+ ions in the laser excitation wavelength of 0,94 microns. The analysis of the obtained relationships and determined the optimal composition of the phosphor (Y1–xYb0,1Erx)3Al5O12.